Critical role of peripheral sensory systems in mediating the neural effects of nicotine following its acute and repeated exposure - Kiyatkin, Eugene A. (Rev Neurosci, 2014)
It is well established that the reinforcing properties of nicotine depend upon its action on nicotinic acetylcholine receptors expressed by brain neurons. However, when administered systemically, nicotine first phasically activates nicotinic receptors located on the afferents of sensory nerves at the sites of drug administration before reaching the brain and directly interacting with central neurons. While this peripheral action of nicotine has been known for years, it is usually neglected in any consideration of the drug’s reinforcing properties and experience-dependent changes of its behavioral and physiological effects. The goal of this work is to review our recent behavioral, electrophysiological, and physiological data, suggesting the critical importance of peripheral actions of nicotine in mediating its neural effects following acute drug exposure and their involvement in alterations of NIC effects consistently occurring following repeated drug exposure. Since nicotine by acting peripherally produces a rapid sensory signal to the CNS that is followed by slower, more prolonged direct drug actions in the brain, these two pharmacological actions interact in the CNS during repeated drug use with the development of Pavlovian conditioned association. This within-drug conditioning mechanism could explain experience-dependent changes in the physiological, behavioral, and human psycho-emotional effects of nicotine, which in drug-experienced individuals always represent a combination of pharmacological and learning variables.